Limerence(being in love) and Violence among Teens/Adults' Relation - Adhikari, Harasankar (Innovare Journal of Social Sciences, 2017)
This paper attempted to examine effect of limerence among teen and adults' relation. Violent behaviors ofÂ  teen and adults are causing various social and relational crises. As consequence of this suicide and other violent illicit work are the causes of unhappiness in daily life of teens/adults. The family/parental relational support would be revitalized for their recovery of mental illness. There is also need of counseling before involvement in love-relation and their emotional decision would be sensitized.